The Relationship Between Structuration Theory and Agency According to Giddens and Walters - Dayrobi, Mhd.; Usqo, Hanafi Urwatil; Lubis, Fauziah (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research aims to understand social action through the lens of Structuration and Agency Theory, with a special focus on the thought of Anthony Giddens and Malcolm Walters. Giddens' Structuration Theory emphasizes the dialectical relationship between agency (individual action) and structure (social rules and resources), where structure not only constrains but also enables action. The concept of duality of structure shows that structure is both the medium and the result of social action. Walters expands this concept by highlighting how individuals, through reflexive capacities, can reproduce or change social structures. This research uses library research methods. The research results show that a deeper understanding of the interaction between agency and structure can enrich sociological analyzes of social change and the sustainability of social structures.